A courtship behavior that makes monandrous females polyandrous. (1st November 2020) - Minekawa, Kazuyoshi; Amino, Kai; Matsuo, Takashi
Abstract: Females of many animal species mate several times with different males (polyandry), whereas females of some species mate with a single male (monandry) only once. Little is known about the mechanisms by which these different mating systems evolve. Females of Drosophila prolongata mate serially, unlike Drosophila melanogaster females that refuse to remate for several days after their first mating (remating suppression [RS]). Nevertheless, interestingly, nonvirgin D. prolongata females refuse to remate with males that are prohibited from performing their species‐specific courtship behavior, leg vibration (LV), suggesting that LV overrides RS making it cryptic in D. prolongata . In this study, we examined how long this cryptic RS persists. Surprisingly, it was sustained for at least 2 weeks, showing that RS is substantially augmented in D. prolongata compared to that of D. melanogaster . The two most closely related species to D. prolongata, Drosophila rhopaloa and Drosophila carrolli, do not perform LV and showed augmented RS, supporting the idea that augmented RS could have evolved before LV was acquired. These results suggested that D. prolongata females are intrinsically monandrous, whereas the newly evolved courtship behavior makes them polyandrous. This is a rare case in which a proximate mechanism of polyandry evolution from monandry is demonstrated.